Injection Site Erythema in a Patient on Therapeutic Anticoagulation with Low Molecular Weight Heparin after Mechanical Aortic Valve Replacement: A Rare Presentation of Heparin- and Protamine-Induced Thrombocytopenia. (10th April 2020) - Holaubek, Caroline; Simon, Paul; Eichinger-Hasenauer, Sabine; Gremmel, Franz; Steinlechner, Barbara
Abstract : Previous exposition to heparin and protamine in patients undergoing cardiopulmonary bypass and postoperative therapeutic anticoagulation with LMWH may lead to the development of heparin-induced thrombocytopenia (HIT) and/or protamine-induced thrombocytopenia (PIT). This case deals with a rare clinical presentation of circulating IgG antibodies against heparin/platelet factor 4 complexes and heparin/protamine complexes after cardiac surgery. Ensuing purpura and skin necrosis (blisters) at the injection sites of LMWH and clinical symptoms improved rapidly after replacement of LMWH by an alternative anticoagulant. The aim of this report is to draw attention to the several different clinical manifestations of heparin- and/or protamine-induced thrombocytopenia and shows a possible course of treatment and recovery.